Modeling the Possible Impacts of Dredging Activities in the Fishery Port of Carocok, Pesisir Selatan Regency, West Sumatra: Hydro-Geo-Oceanographical Approaches - Wisnu Arya Gemilang; Ulung Jantama Wisha; Guntur Adhi Rahmawan; Ilham Ilham; Nia Naenul Hasanah Ridwan (Politeknik Kelautan dan Perikanan Dumai, 2022)
Carocok Fishery Port (PPP Carocok) is a supporting facility for capturing fishery in the Pesisir Selatan Regency. Thus, bathymetry monitoring the shipping lane and the port pool dredging is crucial to bolster fishery activities. This study aims to model the possible impact when massive dredging is applied based on geological and oceanographical approaches. The bottom sediment sampled in the field was analyzed using a granulometric method. A direct bathymetry survey was also done using a single beam echosounder and tide gauge deployment. Hydrodynamic modeling was employed to predict the changes in water motion characteristics if dredging is applied—a scenario applying bathymetry profile after dredging was applied in the simulation. The bathymetry contour within Carocok Bay was relatively declivous, categorized as shallow water with a depth ranging from -2.5 to -15 m. The sediment type in the study area consisted of sand, sandy clay, clayey sand, silty sand, and mixed textures. The tidal current motions (ranging from 0 to 0.053 m/s) are the primary factor transporting the water mass within the port pool, which also impacts sediment transport in the semi-enclosed water area. The sediment characteristics showed that the sediment is deposited in low-energy conditions. It is modeled that the dredging plan in the PPP Carocok will not cause any significant changes, including bathymetry alteration and water environment. Therefore, the port pool is still appropriate to espouse fishery activities in the Carocok Port without dredging.